Mental Models in Science Learning across High School and University Students: A Bibliometric and Systematic Review - Cahyani, Tasya Oktavia Regita; Hamdiyati, Yanti; Rahmat, Adi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
The growing emphasis on conceptual understanding has led to increasing interest in mental models within science education. Despite this development, studies that systematically map research trends, thematic structures, and focal areas across high school and university contexts remain limited. This study examines the evolution of mental model research in science learning by combining bibliometric analysis with a systematic review. Data were drawn from the Scopus database (2015–2025), resulting in 96 articles for bibliometric mapping and 14 articles for in-depth review focused on biology education. The findings indicate a steady rise in publications, with dominant themes centered on conceptual understanding, misconceptions, and assessment development, particularly in physics and chemistry. In contrast, research in biology education remains relatively scarce and largely descriptive, with limited attention to instructional interventions targeting mental model reconstruction. These results underscore the need for studies integrating multiple representations and continuous diagnostic assessment to foster more meaningful biology learning. Model Mental dalam Pembelajaran Sains di Kalangan Siswa Sekolah Menengah Atas dan Universitas: Tinjauan Bibliometrik dan Sistematis ABSTRAK: Peningkatan perhatian terhadap pemahaman konseptual mendorong berkembangnya kajian model mental dalam pendidikan sains. Meskipun demikian, penelitian yang secara sistematis memetakan tren, struktur tematik, dan fokus kajian pada jenjang sekolah menengah dan perguruan tinggi masih terbatas. Penelitian ini bertujuan mengkaji perkembangan riset model mental dalam pembelajaran sains melalui kombinasi analisis bibliometrik dan tinjauan sistematis. Data diperoleh dari basis data Scopus (2015–2025), menghasilkan 96 artikel untuk pemetaan bibliometrik dan 14 artikel untuk kajian mendalam yang berfokus pada pembelajaran biologi. Hasil menunjukkan adanya peningkatan publikasi yang konsisten, dengan tema dominan meliputi pemahaman konseptual, miskonsepsi, dan pengembangan asesmen, khususnya pada bidang fisika dan kimia. Sebaliknya, penelitian pada pembelajaran biologi masih relatif terbatas dan cenderung deskriptif, serta belum banyak mengembangkan intervensi yang menargetkan rekonstruksi model mental. Temuan ini menegaskan perlunya integrasi representasi multipel dan asesmen diagnostik berkelanjutan.